3D-printed Chlorella vulgaris snacks: a contribution to a healthy diet - Oliveira, Sónia; Torres Pérez, María Dolores; Sousa, Isabel; Raymundo, Anabela (Frontiers in Food Science and Technology, 2023)
The aim of the present work was to study the potential health benefits of 3D snacks enriched with increasing levels of incorporation of C. vulgaris (2%–18% w/w). Health impact was evaluated based on the nutritional profile of snacks, as well as protein digestibility, mineral bioaccessibility, glycemic index and antioxidant activity. Higher additions of Chlorella vulgaris to snack’s formulation led to obtain a new food product with elevated nutritional properties, that is a source of protein and minerals, that presents a lower glycemic index, a boosted antioxidant activity and an enhanced mineral bioaccessibility. Despite substantial evidence on the health benefits of microalgae-derived food products, functional food value of algae products remains largely qualitative. The present work contributed to provide insights on bioaccessibility of nutritional compounds of a microalgae food—3D snack–aiming to provide a more sustainable healthy food choice.